2018
DOI: 10.5194/acp-2018-466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transport, mixing, and feedback of dust, biomass burning and anthropogenic pollutants in eastern Asia: A case study

Abstract: 15Anthropogenic fossil fuel (FF) combustion, biomass burning (BB) and desert dust are main sources of air pollutants around the globe. The emission of the three sources in Asia are all very intensive and their influences on air quality is very important, especially in spring. In this study, we investigate the vertical distribution, transport characteristics, source contribution, and meteorological feedback of the dust, BB and FF aerosols in a unique pollution episode occurred in eastern Asia based on various m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…They concluded that cold fronts may be seen as potential carriers of atmospheric pollutants. Similarly, Zhou et al [ 32 ] considered the influence of large-scale cold fronts and warm conveyor belts on the transport of continental aerosols located near the surface mixed with aerosols from the upper planetary boundary layer and middle troposphere. Finally, Song et al [ 33 ] analysed a dust storm event in Northern China in early May 2017 and concluded that the front’s activity was associated with increased wind speed and dust emission.…”
Section: Macroscalementioning
confidence: 99%
“…They concluded that cold fronts may be seen as potential carriers of atmospheric pollutants. Similarly, Zhou et al [ 32 ] considered the influence of large-scale cold fronts and warm conveyor belts on the transport of continental aerosols located near the surface mixed with aerosols from the upper planetary boundary layer and middle troposphere. Finally, Song et al [ 33 ] analysed a dust storm event in Northern China in early May 2017 and concluded that the front’s activity was associated with increased wind speed and dust emission.…”
Section: Macroscalementioning
confidence: 99%
“…In fact, particulate matter and ozone pollution could be frequently observed in this region due to high intensity of human activities (Fu et al., 2008; L. Li et al., 2011). Besides, YRD also suffers from long‐range transported mineral dust from inland source regions such as Gobi Desert, which is often mixed with anthropogenic pollutants (X. X. Zhang et al., 2018; Zhou et al., 2018). Such mixing can contribute to the deterioration of air quality in two ways.…”
Section: Introductionmentioning
confidence: 99%